TEACHING SPEAKING USING TEA PARTY TECHNIQUE - Henny Uswatun Hasanah (OKARA: Jurnal Bahasa dan Sastra, 2017)
Tea party is a technique that is suitable with classroom speaking performance. Since, it forms students into two centeric circles or two lines that face each other, then the teacher gives a question or a topic, the student discuss their answer or ideas concerning to the question or the topic given with the students facing them. After one minute, the outside circle or one line moves to the right side so that students have new partners. Then the teacher pose a second question or topic for them to discuss. Continue with five or move questions. This technique can engage students to speak up as well as keep the students brave to share their idea. Moreover, it lines students up in two lines facing each other. Pose a question to the class, and have students facing each other in the lines discuss the question or topic for a minute or two. Then move on to another question and new partner in the line by having one line move to the right. This activity can also be done in concentric circles, where one circle moves to the right when it is time to get new partners.